Salivary biomarkers in head and neck cancer - Rentroia, Mara Ivone Santos (2019)
Head and neck cancer (HNC) are a group of cancers which occur in the organs from the anatomical area referred. The HNC staging system is generalized for most subtypes of HNC and restricted for the seven classifying stages of this cancer, which affects the diagnosis and, therefore, the treatment. The possible biomarkers identified for HNC are either non-specific or still waiting for clinical validations. Exosomes are nanovesicles which reflect the molecular composition of the cell of origin, including tumour cells, and can be found in biofluids as saliva, a proximal and easily accessible fluid for HNC. As exosome’ purification methods are being developed, the study of the proteome of salivary exosomes of HNC patients is a promising approach for identification of specific biomarkers for HNC and early diagnosis and prognosis of the cancer. In this thesis project, unstimulated saliva was collected from fifteen HNC patients and three healthy subjects and exosomes were extracted. Protein quantification was performed, and the proteins were analysed by LC-MS, after protein separation with SDS-PAGE and in-gel trypsin digestion. The proteomes of salivary exosomes of HNC demonstrated to be involved in a panoply of biological processes mainly focused in exocytosis, inflammatory response and tumour-related processes, which were expected in this study. The overexpression of α-amylase and immunoglobulin A in salivary exosomes of HNC, when compared with the healthy controls, is considered as a potential HNC biomarker. From the several proteins exclusively in either sample 1, 2, 8, 10, 14 and 15, suprabasin, protein S100-A7, S100-P and cathepsin B were already described as HNC possible biomarker in another type of samples. This study demonstrated that the salivary exosomes are capable to reflect the pathophysiological status of HNC. Furthermore, overexpression of α-amylase and immunoglobulin A in salivary exosomes may be a non-specific biomarker of HNC and the previously described HNC biomarkers need to be further studied in order to understand in which conditions they are expressed.